2019
DOI: 10.1136/jech-2019-212268
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle mass in relation to 10 year cardiovascular disease incidence among middle aged and older adults: the ATTICA study

Abstract: BackgroundSkeletal muscle mass (SMM) is inversely associated with cardiometabolic health and the ageing process. The aim of the present work was to evaluate the relation between SMM and 10 year cardiovascular disease (CVD) incidence, among CVD-free adults 45+ years old.MethodsATTICA is a prospective, population-based study that recruited 3042 adults without pre-existing CVD from the Greek general population (Caucasians; age ≥18 years; 1514 men). The 10 year study follow-up (2011–2012) captured the fatal/non-fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 38 publications
1
64
0
Order By: Relevance
“…sarcopenia are associated with increased risk of CVD (26)(27)(28)(29)(30) . It is well documented that sarcopenia is a significant predictor of death in older adults, including those who are community-dwelling, care home residents or hospitalised patients (31)(32)(33) .…”
mentioning
confidence: 99%
“…sarcopenia are associated with increased risk of CVD (26)(27)(28)(29)(30) . It is well documented that sarcopenia is a significant predictor of death in older adults, including those who are community-dwelling, care home residents or hospitalised patients (31)(32)(33) .…”
mentioning
confidence: 99%
“…guidelines are followed. Given the association of low muscle mass and function with morbidity and mortality [30][31][32], underestimating the prevalence of sarcopenia will likely have more dire consequences and higher health care costs in the long run. SARC-F has poor sensitivity but high speci city for sarcopenia de nitions including FNIH and EWGSOP1 [33] and may detect severe cases [18].…”
Section: Discussionmentioning
confidence: 99%
“…(iii) Taken together, these findings might suggest a link of gut microbiota composition and cardiometabolic health. Central obesity, for example, high waist-height ratio, has been identified as a risk factor for cardiovascular disease mortality [43], whereas muscle mass seems to protect from cardiovascular disease [44]. Additionally, previous studies already have shown associations of the gut microbiome with cardiometabolic risk factors [45] and are supported by mechanistic studies in mice, suggesting a role for gut bacteria in dietary energy harvest and fatty acid metabolism [41].…”
Section: Adiposity Measurement Selectionmentioning
confidence: 97%